The off-label drug use in oncology and hematology with emphasis on age groups - Gil, Lidia; Styczyński, Jan; Wysocki, Mariusz; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2005)
Drug approval refers to indications, patient characteristics, dosage, route of administration, contraindications and warnings. The term „off-label prescribing” refers to the use of a drug outside the terms of its marketing authorization, including prescribing for an unlicensed indication. In this review, we analyzed the extent of the off-label use in childhood and adult hemato-oncology patients, based on the PubMed database. Prescribing for non-approved uses is widespread in different medicine areas. The frequency of off-label prescriptions among pediatric oncological patients was estimated to be 36-46%, whereas for adult patients with cancer at the level 22-33%. The most common reasons for the off-label use in children were lack of adequate formulations, which facilitate administration of the doses which small children require and lack of drug registration for children while registration for adult patients is completed. In adults, most common reasons were related to indications, dosage and route of drug administration. The off-label drug use creates an important medical, economic and ethical problem and also causes therapy reimbursement difficulties. This problem requires immediate regulatory intervention, but also a more evidence-based therapeutic approach. Possibilities of solving the off-label use include shortening of the drug approval process and faster update process related to results of new clinical trials.